2019
DOI: 10.1111/jne.12796
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria modulatory effects of new TSPO ligands in a cellular model of tauopathies

Abstract: Translocator protein 18 kDa (TSPO) is a mitochondrial protein located in the outer membrane and involved in cholesterol translocation, a prerequisite for steroid biosynthesis. TSPO modulation also appears to play a role in other mitochondrial functions, including mitochondrial respiration and cell survival. In the central nervous system, its expression is up‐regulated in neuropathology such as Alzheimer's disease (AD). Previously, we demonstrated that two new TSPO ligands, named 2a and 2b, stimulated pregnenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 45 publications
3
39
0
Order By: Relevance
“…Neurosteroids are also able to modulate neuronal bioenergetics by increasing mitochondrial respiration and ATP production, at least in part via nuclear steroid receptor activation [ 36 ]. Our recent findings revealed that the P5 levels were decreased in cellular models of AD, together with impairments in mitochondrial bioenergetics [ 37 , 38 ]. Strikingly, treatment with TSPO ligands increased P5 production and improved mitochondrial energy production in the presence of AD-related pathological proteins, amyloid-β peptide, and abnormal Tau protein.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosteroids are also able to modulate neuronal bioenergetics by increasing mitochondrial respiration and ATP production, at least in part via nuclear steroid receptor activation [ 36 ]. Our recent findings revealed that the P5 levels were decreased in cellular models of AD, together with impairments in mitochondrial bioenergetics [ 37 , 38 ]. Strikingly, treatment with TSPO ligands increased P5 production and improved mitochondrial energy production in the presence of AD-related pathological proteins, amyloid-β peptide, and abnormal Tau protein.…”
Section: Discussionmentioning
confidence: 99%
“…These ligands could also stabilise mitochondrial respiration under stress conditions, and ultimately reduce levels of amyloid beta formation [64]. These novel ligands have also been found to increase levels of ATP production and stabilise mitochondrial membrane potential unrelated to any effects on steroidogenesis [65]. TSPO ligands have also demonstrated analogous effects in other immune cell types, as PK11195 was shown to reduce basal ROS generation in mouse primary peritoneal macrophages [66], and Ro5-4864 has been shown to preserve mitochondrial membrane potential and reduce ROS production after glucose deprivation stress in astrocytes, compared to controls [67].…”
Section: Tspo and Redox Mechanismsmentioning
confidence: 99%
“…In particular, phospho-tau interaction with VDAC was evident in the brain of AD patients at different Braak stages (I to V), as well as in 13-months-old APP/PS1 and 3xTgAD transgenic mice [ 145 ]. Furthermore, in our recent study, we showed that TSPO ligands increased the ΔΨm in htau- and P301L tau-overexpressing SH-SY5Y cells [ 131 ]. We speculated that this effect was mediated by the ability of these ligands to modulate the mPTP, although further investigations need to be conducted to determine the exact underlying mechanisms.…”
Section: Mitochondria: Target Of Taumentioning
confidence: 99%
“…We recently showed that abnormal tau also disturbs another mitochondrial function: the synthesis of neurosteroids or neurosteroidogenesis [ 131 ]. Indeed, steroids can be synthesized de novo in the brain from cholesterol, independently of the peripheral steroidogenic glands, and are then called “neuro”-steroids (reviewed in [ 148 ]).…”
Section: New Insight On the Impact Of Abnormal Tau On Neurosteroidmentioning
confidence: 99%
See 1 more Smart Citation